2023
DOI: 10.1111/bpa.13192
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral macrophages drive CNS disease in the Ndufs4(−/−) model of Leigh syndrome

Abstract: Subacute necrotizing encephalopathy, or Leigh syndrome (LS), is the most common pediatric presentation of genetic mitochondrial disease. LS is a multi‐system disorder with severe neurologic, metabolic, and musculoskeletal symptoms. The presence of progressive, symmetric, and necrotizing lesions in the brainstem are a defining feature of the disease, and the major cause of morbidity and mortality, but the mechanisms underlying their pathogenesis have been elusive. Recently, we demonstrated that high‐dose pexida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Since the first trial of vatiquinone started in 2012, significant progress has been made in identifying therapeutic targets in the mouse model. Most notably chronic mild hypoxia and immune targeting show significant promise ( 8 , 10 , 25 30 ). We believe that strategies showing efficacy in a robust animal models should be prioritized over those lacking in vivo evidence, and that agents with known mechanism of action should be prioritized over those whose targets are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first trial of vatiquinone started in 2012, significant progress has been made in identifying therapeutic targets in the mouse model. Most notably chronic mild hypoxia and immune targeting show significant promise ( 8 , 10 , 25 30 ). We believe that strategies showing efficacy in a robust animal models should be prioritized over those lacking in vivo evidence, and that agents with known mechanism of action should be prioritized over those whose targets are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to what occurs with whole‐body or neuronal‐specific knockouts, concrete mechanisms by which particular mitochondrial malfunctions in astrocytes lead to disease (e.g., loss of astrocytic trophic support to neurons, reactive astrocytes generating an exacerbated inflammatory environment detrimental to neurons) are unknown. On the other hand, recent reports using the Ndufs4 KO mouse model of Leigh syndrome demonstrated that both microglia and other peripheral myeloid cells greatly contribute to the disease pathogenesis found in Ndufs4 KO mice 88–90 . Although the precise immune pathways governing the pathological contributions of these cells have not yet been deciphered, these reports postulate that immune‐related responses could be a pathological mechanism to consider in other mouse models of PMDs and in patients.…”
Section: Neuroinflammation As a Potential Pathogenic Mechanism In Pmdsmentioning
confidence: 99%
“…We propose that the potential for neuroinflammation to play a role is intriguing, given that neuroinflammation and neuroimmune responses are widely known contributors to the pathology of other neurodegenerative diseases 66 . In this regard, only a few studies have focused on the direct role of astrocytes, 84–87 microglia, 88,89 peripheral myeloid cells, 90 or chronic neuroinflammation 91 . On the one hand, reports using astrocytic mitochondrial dysfunction models have shown that in some cases not solely neuronal mitochondrial abnormalities are responsible for a particular disease.…”
Section: Neuroinflammation As a Potential Pathogenic Mechanism In Pmdsmentioning
confidence: 99%
“…Additionally, in mouse models of mitochondrial-related myopathies, mtDNA has been shown to promote inflammation and muscle atrophy [ 15 , 16 ]. Furthermore, recent studies have highlighted the emerging role of microglia and peripheral immune cells in the development of the Ndufs4 KO encephalopathy, a mouse model of Leigh syndrome (LS) [ 17 19 ]. Immune-related processes have not only been speculated to directly guide the pathology in MDs, but also to influence their onset and their degree of progression [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%